2012
DOI: 10.1038/pr.2012.73
|View full text |Cite
|
Sign up to set email alerts
|

Sleep fragmentation and intermittent hypoxemia are associated with decreased insulin sensitivity in obese adolescent Latino males

Abstract: Background Although sleep-related breathing disorder (SRBD) has been linked to insulin resistance in adults, this has not been as well established in children. We hypothesized that the severity of SRBD in adolescents was associated with metabolic impairment. Methods Polysomnography was performed on obese, Latino males referred for snoring. The frequently sampled intravenous glucose tolerance test (FSIVGTT) was used to assess glucose homeostasis. Total body dual-energy X-ray absorptiometry (DEXA) was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 35 publications
4
29
1
3
Order By: Relevance
“…After adjustment for prepregnancy BMI, higher microarousal index and more frequent oxygen desaturation events were associated with higher fasting glucose levels. These associations between sleep disturbances and reduced glucose tolerance are in agreement with those in nonpregnant populations (3,22,23).…”
Section: Discussionsupporting
confidence: 79%
“…After adjustment for prepregnancy BMI, higher microarousal index and more frequent oxygen desaturation events were associated with higher fasting glucose levels. These associations between sleep disturbances and reduced glucose tolerance are in agreement with those in nonpregnant populations (3,22,23).…”
Section: Discussionsupporting
confidence: 79%
“…4,5,15,16 This study investigated whether DEXA scans could be used to show that a sensitive measure of fat mass and distribution of fat correlates with SRBD in obese/ overweight pediatric patients. We found that total body fat mass and trunk fat mass as measured on DEXA scanning, as well as BMI, were associated with total arousal index and desaturation index.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In the pediatric age group, it has been associated with signifi cant metabolic and autonomic dysfunction. [3][4][5] In children obesity has been shown to be an independent risk factor for snoring and obstructive sleep apnea (OSA). 6,7 The literature also provides evidence regarding the predictors of SRBD in obese children.…”
mentioning
confidence: 99%
“…[10,11] By contrast, sleep dysfunction is linked to the development of physical and psychological issues including cardiovascular problems, diabetes, obesity, anxiety, and all-cause high rates of death [12] and number of studies have supported that the metabolic rate related to interference of normal sleep behaviors may related to the development of obesity, cardiovascular disease, diabetes, and diabetes. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] In the current study, the authors applied crosssectional study that explore the association between Body Mass Index (BMI) and sleep pattern among undergraduate female students of health colleges in Qassim University.…”
Section: Introductionmentioning
confidence: 99%